The Impact of Agricultural Bioplastic Use and Farmers’ Environmental Awareness on Reducing Plastic Waste in West Java’s Horticultural Centers - Indriyani Indriyani; Dila Padila Nurhasanah; Rani Eka Arini (Westscience Press, 2026)
The extensive use of conventional plastic materials in horticultural farming has contributed to increasing environmental pollution and agricultural waste accumulation. Sustainable alternatives such as agricultural bioplastics, combined with farmers’ environmental awareness, are considered important factors in reducing plastic waste generated from agricultural activities. This study aims to analyze the impact of agricultural bioplastic use and farmers’ environmental awareness on plastic waste reduction in horticultural centers in West Java. A quantitative research approach was employed using a survey method involving 200 horticultural farmers selected through purposive sampling. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using SPSS Version 25. The analytical techniques included descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing through t-tests and F-tests. The results indicate that agricultural bioplastic use has a positive and significant effect on plastic waste reduction. Farmers’ environmental awareness also demonstrates a positive and significant effect on plastic waste reduction. Simultaneously, both variables significantly influence plastic waste reduction, with a coefficient of determination (R²) of 0.428, indicating that 42.8% of the variation in plastic waste reduction is explained by the model. These findings suggest that the integration of environmentally friendly agricultural technologies and environmental awareness initiatives can effectively reduce plastic waste and support sustainable horticultural production. The study highlights the importance of promoting agricultural bioplastics and strengthening environmental education programs to improve environmental sustainability in agricultural communities.